2015
DOI: 10.1055/s-0035-1554659
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acoustic Radiation Force Impulse Imaging (ARFI) for the Determination of Liver Stiffness Using Transient Elastography as a Reference in Children

Abstract: Purpose: Transient elastography (Fibroscan?; (FS)) and acoustic radiation force impulse imaging (ARFI) represent noninvasive, user-friendly and quick methods providing an objective and reproducible measure of liver stiffness. The aim of the study was to evaluate cut-off values and performance of ARFI measurements in children using transient elastography as a reference. Methods/Patients: A total of 198 children were enrolled in this study. All patients underwent liver stiffness measurements with FS (FS-LS) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Engelmann et al [12] established the values of stiffness median for age group 0-5 years, 4.40 kPa; for age group 6-11 years, 4.73 kPa; and for age group 11-18 years, 5.10 kPa (p = 0.001). Sagir et al [15] also observed age and stiffness dependence: 4.8 ± 1.4 kPa (0-5 years), 5.6 ± 1.3 kPa (6-11 years), and 5.7 ± 1.7 kPa (12-18 years). Stiffness values in these age groups coincided with the results obtained in our study.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Engelmann et al [12] established the values of stiffness median for age group 0-5 years, 4.40 kPa; for age group 6-11 years, 4.73 kPa; and for age group 11-18 years, 5.10 kPa (p = 0.001). Sagir et al [15] also observed age and stiffness dependence: 4.8 ± 1.4 kPa (0-5 years), 5.6 ± 1.3 kPa (6-11 years), and 5.7 ± 1.7 kPa (12-18 years). Stiffness values in these age groups coincided with the results obtained in our study.…”
Section: Resultsmentioning
confidence: 86%
“…Statistically significant differences between subgroups 2 and 3 were not established (p > 0.001). Thus, liver stiffness values in children older than 6 years [15] who studied normal indices of stiffness by transient elastography method in groups of 240 and 198 children. Engelmann et al [12] established the values of stiffness median for age group 0-5 years, 4.40 kPa; for age group 6-11 years, 4.73 kPa; and for age group 11-18 years, 5.10 kPa (p = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Other articles do include healthy children as a control group, but the samples are small (4,8,9). Therefore, our goal was to determine the potential benefits and limitations of the two probes in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…p -SWE is mainly used to determine liver stiffness, which is then used for the staging of cirrhosis (3)(4)(5). To assess liver chirrosis or splenic stiffness, a convex probe is usually used (6)(7)(8)(9). Because of shortage of superficial fat tissue in pediatric patients, a linear probe with a higher frequency could easily be used.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric studies have revealed that the improved diagnostic accuracy of liver fibrosis can be reached using a combination of non-invasive methods[ 83 , 97 ]. Therefore, more and more studies in children concern the clinical utility of combining 2 or more non-invasive fibrosis tests in children, and the first studies aimed at comparing the diagnostic performance of 2 imaging methods in a group of children to evaluate its correlation and utility in assessing liver fibrosis have been conducted[ 101 ].…”
Section: Physical Techniquesmentioning
confidence: 99%